2022
DOI: 10.1016/j.ssmmh.2021.100054
|View full text |Cite
|
Sign up to set email alerts
|

Gender disparity in telehealth usage in Bangladesh during COVID-19

Abstract: Background and aims Telehealth allows healthcare workers to see patients virtually in locations that were not accessible previously, which has reduced cost and time and saved lives. The research aims to examine gender disparity among telehealth usage during the pandemic in 2020. This study will leverage a timely national experiment to evaluate the users of telehealth across the Bangladeshi population. Methods We obtained de-identified data for 200 patients among outpati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 10 publications
1
9
0
Order By: Relevance
“…A total of 550 patients participated in this study—most were male, aged 18 to 25 years, single, from a high-income family, and highly educated. This reflects the literature suggesting that low education, poverty, older age, and being female are discriminatory barriers to telemedicine use [ 42 ]. Telephone calls were the most common mode of telemedicine.…”
Section: Discussionsupporting
confidence: 74%
“…A total of 550 patients participated in this study—most were male, aged 18 to 25 years, single, from a high-income family, and highly educated. This reflects the literature suggesting that low education, poverty, older age, and being female are discriminatory barriers to telemedicine use [ 42 ]. Telephone calls were the most common mode of telemedicine.…”
Section: Discussionsupporting
confidence: 74%
“…China [ 111 , 112 ], India [ 113 , 114 ], Norway [ 115 , 116 ], and Thailand [ 117 , 118 ] were each represented in 2 (2.3%) papers. Other countries represented were Bangladesh [ 119 ], the Czech Republic [ 120 ], Denmark [ 121 ], the United Kingdom [ 122 ], Greece and Finland (a joint paper) [ 123 ], Italy [ 124 ], Jamaica [ 125 ], Libya [ 126 ], Saudi Arabia [ 127 ], South Africa [ 128 ], and Turkey [ 129 ].…”
Section: Resultsmentioning
confidence: 99%
“…Our ndings related to sex coincide with the data published by Rahman et al in Bangladesh, who found a profound gender disparity in the Telemedicine use during the COVID-19 pandemic, with fewer females than males. The reasons given by the authors include the difference in education levels and technical literacy in using online platforms for telehealth services (20).…”
Section: Discussionmentioning
confidence: 99%